(untitled) (International Journal of Engineering and Computer Science, 2014)
Large scale distributed systems such as Cloud Computing applications are becoming very common these days. These applications come with increasing challenges on how to transfer and where to store and compute data. The most prevalent distributed file systems to deal with these challenges are the Hadoop File System (HDFS) which is a variant of the Google File System (GFS). However HDFS has two potential problems. The first one is that it depends on a single name node to manage almost all operations of every data block in the file system. As a result, it can be a bottleneck resource and a single point of failure. The second potential problem with HDFS is that it depends on TCP to transfer data. As has been cited in many studies, TCP takes many rounds before it can send at the full capacity of the links in the cloud. These results in low link utilization and longer download times. To overcome these problems of HDFS, a new distributed file system is presented in this thesis. The scheme of this distributed file system uses a light weight front end server to connect all requests with many name nodes i.e. Triple Security.